2005
DOI: 10.1002/hlca.200590129
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfonamide Derivatives as Inhibitors of Histone Deacetylase

Abstract: Dedicated to Professor Rolf Huisgen on the occasion of his 85th birthday Inhibition of the enzyme histone deacetylase (HDAC) is emerging as a novel approach to the treatment of cancer. A series of novel sulfonamide derivatives were synthesized and evaluated for their ability to inhibit human HDAC. Compounds were identified which are potent enzyme inhibitors, with IC 50 values in the low nanomolar range against enzyme obtained from HeLa cell extracts, and with antiproliferative effects in cell culture. Extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
(13 reference statements)
0
39
0
Order By: Relevance
“…This reported synthesis was inspired by a previously published synthesis of belinostat [16] where 2-(4-amino-benzyl)-malonic acid dimethyl ester was reacted with 1 instead of aniline. The sulfonyl chloride compound, 1, was reacted with 2- respectively.…”
Section: Synthesis Of Mal-p-belmentioning
confidence: 99%
See 1 more Smart Citation
“…This reported synthesis was inspired by a previously published synthesis of belinostat [16] where 2-(4-amino-benzyl)-malonic acid dimethyl ester was reacted with 1 instead of aniline. The sulfonyl chloride compound, 1, was reacted with 2- respectively.…”
Section: Synthesis Of Mal-p-belmentioning
confidence: 99%
“…[15] Though the arylsulfonamide group in belinostat is meta substituted we selected the para analogue (p-Bel, Figure 2) for our study on the basis that it has comparable HDAC inhibitory and anti-proliferative activity as compared to belinostat but its synthesis is more facile. [16] We sought to derivatise p-Bel with a dicarboxylate linker so as to facilitate its binding to and hydrolysis from a cis-diammine Pt(II) moiety. We utilised molecular modelling to identify which p-Bel to develop with a view to facilitating complexation to Pt while minimising any negative impact on HDAC inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…2, 172.0, 137.1, 135.7, 135.3, 129.5, 129.2, 128.5, 128.4, 128.3, 128.1, 126.7, 67.3, 61.0, 57.0, 52.7, 48.3, 39.4 H 5.76, N 6.38; found: C 59.18, H 5.87, N 6.27. (6) 3, 172.1, 140.6, 135.3, 128.5, 128.4, 128.3, 128.1, 126.1, 67.3, 61.9, 61.4, 56.0, 48.6, 35.2, 31.7, 31 6, 135.3, 128.5, 128.4, 128.3, 128.1, 126.1, 67.3, 61.9, 61.4, 56.0, 48.6, 35.2, 31.7, 31 3067, 3034, 2954, 2881, 1743, 1638, 1455, 1330, 1148, 1017, 849 cm -1 ; 1 H-NMR (CDCl 3 ) δ 7.52-7.30 (m, 5H), 7.24-7.14 (m, 1H), 7.00-6.83 (m, 2H), 5.29-5.11 (m, 2H), 4.75-4.60 (m, 1H), 4.52-4.42 (m, 1H), 3.53-3.28 (m, 4H), 3.04 (t, J = 6.5 Hz, 2H), 2.36-2.24 (m, 1H), 2.12-1.90 (m, 3H); 13 C-NMR (CDCl 3 ) δ 172. 5, 140.5, 135.3, 128.6, 128.4, 128.3, 127.0, 125.6, 124.0, 67.3, 61.3, 48.7, 44.7, 31.3, 30.6, 25 Anal.…”
Section: General Procedures For Coupling Reaction Of Chlorosulfonyl-l-mentioning
confidence: 99%
“…More recently, the Angibaud group [5] reported the preparation of a series of pyrimidyl-5-hydroxamic acids having significant HDAC activity in human tumor cell lines. The Kalvinsh group [6] demonstrated that a series of novel sulfonamide derivatives were synthesized and evaluated for their ability to inhibit human HDAC. The Delorme group [7] developed of potential antitumor agents as a new set of sulfonamide derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization of TLC plates was made with short wave (254 nm) UV light. Flash column chromatography was carried out using silica gel 0.035-0.070 mm (Merck (8h), 3-formyl-indole-1-carboxylic acid tert-butyl ester 21 (8a), 3-formyl-N-phenyl-benzenesulfonamide 22 (8i), were synthesized according to literature procedures.…”
Section: Chemistrymentioning
confidence: 99%